2018
DOI: 10.1111/sipr.12054
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Experiences and Intergroup Biases among Children

Abstract: Children show signs of intergroup biases from early in development, and evidence suggests that these biases increase through middle childhood. Here we critically review and synthesize the literature on the different types of childhood experiences that have been associated with increases or decreases in childhood intergroup bias. Based on the review, one type of childhood experience stands out as being reliably associated with increased intergroup bias over multiple studies-specific overt messages communicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 151 publications
3
62
1
4
Order By: Relevance
“…One limitation of the current study is that we did not assess the quality of (parents' or children') contact (e.g., the nature and closeness of their interracial friendships). Although our primary measures of intergroup contact (i.e., number of Black friends, frequency of contact) are consistent with previous work that has assessed intergroup contact as a covariate (e.g., Greenwald, McGhee, & Schwartz, 1998), we recognize that much research on intergroup contact suggests that the quality of the contact is also important to consider (Cameron, Rutland, Hossain, & Petley, 2011;Gaither & Sommers, 2013;Skinner, & Meltzoff, 2019). Moreover, given that people's self-reports about their explicit negative attitudes toward various social groups are influenced by social desirability concerns, it is possible that more indirect, or implicit, measures may tell a different story about the relation between racial attitudes and socialization (Greenwald et al, 1998).…”
Section: Limitationssupporting
confidence: 80%
See 1 more Smart Citation
“…One limitation of the current study is that we did not assess the quality of (parents' or children') contact (e.g., the nature and closeness of their interracial friendships). Although our primary measures of intergroup contact (i.e., number of Black friends, frequency of contact) are consistent with previous work that has assessed intergroup contact as a covariate (e.g., Greenwald, McGhee, & Schwartz, 1998), we recognize that much research on intergroup contact suggests that the quality of the contact is also important to consider (Cameron, Rutland, Hossain, & Petley, 2011;Gaither & Sommers, 2013;Skinner, & Meltzoff, 2019). Moreover, given that people's self-reports about their explicit negative attitudes toward various social groups are influenced by social desirability concerns, it is possible that more indirect, or implicit, measures may tell a different story about the relation between racial attitudes and socialization (Greenwald et al, 1998).…”
Section: Limitationssupporting
confidence: 80%
“…Prior work has shown little evidence of overlap between the racial attitudes of parents and their children, which has been speculated to be a result of the lack of explicit conversations about race in most White families (Skinner & Meltzoff, 2019;Vittrup, 2018). Thus, although parents in the current study reported fairly positive attitudes toward Black people, their children may have little knowledge of their parents' attitudes in the absence of explicit conversations about race.…”
Section: Discussioncontrasting
confidence: 54%
“…Prejudice interventions in children have shown to be particularly effective when including intergroup contact (Allport, ) or education and anti‐bias communication (Bigler & Liben, ), although effects can vary according to age and target outgroup (for reviews see Aboud et al, ; Raabe & Beelmann, ; Skinner & Meltzoff, ; Ülger et al, ). In line with the social‐cognitive developmental perspective on prejudice (Rutland et al, ), these interventions with a focus on changing children’s context in turn influence emotional and cognitive processes (e.g., higher empathy, fewer stereotypes) (Aboud et al, ) to counteract the development of prejudice.…”
Section: Prejudice Interventions In Childhoodmentioning
confidence: 99%
“…The social‐cognitive developmental perspective on prejudice (Rutland, Killen, & Abrams, ) argues that prejudice develops from a complex interplay between socio‐cognitive (i.e., morality) and socio‐contextual (i.e., group processes) factors. Prejudice‐interventions in children based on intergroup contact theory (Allport, ) have been shown to be particularly effective (Aboud et al, ; Raabe & Beelmann, ; Skinner & Meltzoff, ; Ülger, Dette‐Hagenmeyer, Reichle, & Gaertner, ). However, as very young children have less control over their social environments and therefore may have little opportunities to seek direct outgroup contact, more indirect intergroup contact forms such as mentally simulating positive outgroup contact (imagined contact, Crisp & Turner, ) may be more effective in tackling prejudice in early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…The general idea is that by familiarizing people from diverse groups to each other, they would come to realize that: (a) out‐groups are not composed of homogeneous members all sharing some deep essential features, but rather are composed of unique individuals as diverse as in‐groups, and (b) out‐group members are not that different from in‐group members, often times sharing the same interests, values, and habits. And indeed, intergroup contact has proven fairly effective among adults (see Hodson, Crisp, Meleady, & Earle, ; Pettigrew & Tropp, , for reviews), and children (see Beelmann & Heinemann, ; Skinner & Meltzoff, , for reviews). For instance, studies in the United States and the U.K. have shown that cross‐race friendships or racially heterogeneous kindergartens and schools, have positive effects on children's racial attitudes and stereotypes (Feddes, Noack, & Rutland, ; McGlothlin, Edmonds, & Killen, ; Ruck, Park, Crystal, & Killen, ; Rutland, Cameron, Bennett, & Ferrell, ; Tropp & Prenovost, ), and Jewish and Arab Israeli children attending integrated schools become less essentialists about ethnic differences than their age‐mates attending segregated schools (Deeb, Segall, Ben‐Eliyahu, & Diesendruck, ).…”
Section: Introductionmentioning
confidence: 99%